Employee Readiness for Change Through the Lens of The Cultural Self-Representation Theory - Hechanova, Ma. Regina (Archīum Ateneo, 2012)
Change is imperative in organizations. One fundamental tool in instigating innovation is change management. Employee engagement is seen as a primary ingredient in successfully triggering readiness to change. However, beyond change management, culture is important in influencing employee engagement and readiness to change. Research suggests that Filipino employees, who generally possess a collectivist cultural orientation, are more motivated when working in groups. Therefore, good working relations are important in eliciting engagement among them. This study hypothesizes that both change management and samahan (a Filipino concept on quality of relationships) is mediated by engagement, which brings about readiness for change. Furthermore, change management correlates to samahan. A survey involving Filipino organizations was conducted. The hypotheses were tested using structured equation modeling. Results revealed significant relationship between samahan and change management. Also, employee engagement mediated the relationships of both change management and readiness for change, and samahan and readiness for change. Furthermore, samahan predicted employee engagement more than change management. The study highlights the importance of quality relationships in employee engagement leading to readiness for change. Lastly, this study adds to the growing knowledge base of Filipino researches on the importance of understanding organization behavior using an indigenous concept.